The teachings of John Paul II and the paradoxes of the right to life in the International Human Rights discourse - Lafferrière, Jorge Nicolás (2023)
Fil: Lafferrière, Jorge Nicolás. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina